Analysis of two-party salary negotiations: factos impeding a mutually-beneficial joint agreement - Lombera, David Carrillo (2007)
Business professionals were surveyed to explore both factors associated with negotiation propensity, as well as the strategies used by employees and employers in salary negotiations. The objective is to examine the factors that impede both pasties in reaching a mutually-beneficial joint agreement in salary negotiations. In order to achieve this objective, a review of the negotiations literature was conducted including both. Descriptive literature - present research finding and scientific theory which characterizes negotiation and examines the forces that determine it's course and outcome - as well as a review of the prescriptive literature - in order to develop practical advice given a description of hw negotiators behave. Research result show that, although there is general tendency for employers to leave room in the first offer for negotiation, employees rarely ask for more and generally accept the first offer. The sub-optimal outcome was partially a result of the employees' preferred strategies for negotiation salary: a soft approach focusing on compromised and maintaining the relationship. An analysis of the results combined with the literature explore, demonstrates that both parties exhibited a fixed-pie perspective, focusing on salary as the key issue, which impeded the search for integrative settlements and, mutually beneficial trade-offs.